Kualitas Pelayanan Keperawatan dan Hubungannya dengan Kepuasan Pasien di UPTD. Puskesmas Maritaing : Quality of Nursing Services and Its Relationship with Patient Satisfaction at UPTD. Maritaing Community Health Center - Salil, Gabrie (MPI Press, 2023)
Introduction: Hospitals or Puskesmas are faced with competitive challenges and a competitive environment. Hospitals or Public Health Center are required to provide quality nursing services so that they can meet patient expectations and satisfaction. Objectives: The purpose of this study was to describe the quality of nursing services and the level of patient satisfaction and to know the relationship between the quality of nursing services and patient satisfaction in the UPTD. Maritaing Public Health Center, Alor Regency, East Nusa Tenggara Province. Methode: The type of research used in this research is descriptive and correlative. The sample in this study was 80 patients in the inpatient room. The sampling method in this study used a purposive sampling technique. The instruments used in this study were demographic questionnaires, nursing service quality questionnaires, and inpatient satisfaction questionnaires. Test the hypothesis by using the chi-square test. Result: The results of research that has been carried out in the inpatient UPTD. Puskesmas Maritaing can conclude that the average value for the quality of nursing services is 64, which is included in the good quality category with an interval of 60.1 – 80, the average value for patient satisfaction is 67.8, which is included in the satisfied category with a value interval of 60.1 – 80, while Based on the results of the analysis with the chi-square correlation test, it is known that the Asymptotic Significance value is 0.000 = 0.05, namely 0.000, which means Ho is rejected and Ha is accepted. Conclusion: There is a strong and significant influence between the quality of nursing services and the level of patient satisfaction in the UPTD inpatient room. Maritaing Health Center, Alor Regency, East Nusa Tenggara Province.